'Production' and 'Reproduction' in Feminism: Ideas, Perspectives and Concepts. (January 2014) - Paltasingh, Tattwamasi; Lingam, Lakshmi
The article examines the concept of 'production' and 'reproduction' within the feminist discourse. It aims at examining some of the important issues which have emerged in the debates concerning sexual division of labour and the organization of gender relations prevailing within the family and in a larger social structure. The conceptual framework for analyzing 'production' and 'reproduction' is discussed. Then, an analysis of these concepts is carried out through an account of the major feminist schools of thought. Thereafter, the interlinkage between production and reproduction in the light of maintenance and perpetuation of women's subordination is examined by understanding the relationship between the market and family, between the production of things and the production of people and between patriarchy and capitalism. The article also attempts to arrive at a perspective in understanding the situation of women in contemporary India.